Pengembangan Media Pembelajaran Interaktif Berbasis Kontekstual : Literature Review untuk Meningkatkan Penguasaan Konsep Laju Reaksi dan Karakter Siswa SMA - Faiga Olifia Dg. Mangawe; Masrid Pikoli; Erni Mohamad; Lukman A.R. Laliyo; Erga Kurniawati (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This research focuses on the development of contextual-based interactive learning media to improve mastery of reaction rate concepts and develop the character of high school students in remote areas. This learning media was developed to provide learning experiences that are relevant to everyday life, therefore the concepts of reaction rate are simpler to understand and apply in students. In addition, this contextual approach also aims to encourage character development, such as responsibility, discipline, creativity, curiosity, and communicativeness during the learning process. A literature review was conducted to gather articles relevant to this topic, with a published time frame of 2018 - 2025. The review shows that this media significantly helps students in understanding the concept of learning material, critical thinking, as well as strengthening positive character aspects that support learning success. This research concludes that contextual-based interactive learning can be an efficient option in the science learning process in high school.